ProSNEx: a web-based application for exploration and analysis of protein structures using network formalism - ÖZBEK SARICA, PEMRA (OXFORD UNIV PRESS, 2019)
ProSNEx (Protein Structure Network Explorer) is a web service for construction and analysis of Protein Structure Networks (PSNs) alongside amino acid flexibility, sequence conservation and annotation features. ProSNEx constructs a PSN by adding nodes to represent residues and edges between these nodes using user-specified interaction distance cutoffs for either carbon-alpha, carbon-beta or atom-pair contact networks. Different types of weighted networks can also be constructed by using either (i) the residue-residue interaction energies in the format returned by gRINN, resulting in a Protein Energy Network (PEN); (ii) the dynamical cross correlations from a coarse-grained Normal Mode Analysis (NMA) of the protein structure; (iii) interaction strength. Upon construction of the network, common network metrics (such as node centralities) as well as shortest paths between nodes and k-cliques are calculated. Moreover, additional features of each residue in the form of conservation scores and mutation/natural variant information are included in the analysis. By this way, tool offers an enhanced and direct comparison of network-based residue metrics with other types of biological information. ProSNEx is free and open to all users without login requirement at http://prosnex-tool.com.
Keywords: MOLECULAR-DYNAMICS SIMULATIONS; EVOLUTIONARY CONSERVATION; ALLOSTERIC COMMUNICATION; SINGLE-PARAMETER; DATA-BANK; MODELS; SERVER; VISUALIZATION; MOTIONS; CONSURF